Geissoschizine methyl ether protects oxidative stress-mediated cytotoxicity in neurons through the 'Neuronal Warburg Effect'. (1st July 2016) - Sun, Jiahong; Ren, Xuefang; Qi, Wen; Yuan, Dan; Simpkins, James W.
Abstract: Ethnopharmacological relevance: The rate of production of reactive oxygen species (ROS) is determined by mitochondrial metabolic rate. In turn, excessive ROS damage mitochondrial function, which is linked to aging and neurodegenerative conditions. One possible path to prevent oxidative stress could be achieved by reducing mitochondrial respiration in favor of less efficient ATP production via glycolysis. Such a shift in energy metabolism is known as the 'Warburg effect'. Geissoschizine methyl ether (GM) is one of the active components responsible for the psychotropic effects of Yokukansan, an herbal preparation widely used in China and Japan. Aim of the study: GM protects neurons from glutamate-induced oxidative cytotoxicity through regulating mitochondrial function and suppressing ROS generation. We investigated the protective mechanism of GM against glutamate-induced oxidative stress in neuronal cells. Materials and methods: The current study was performed on primary neurons and HT22 cells, a hippocampus neuronal cell line. Cell viability was measured by Calcein AM assay. H2 DCFDA staining was used for intracellular ROS measurement. GSH level was measured using the GSH-Glo™ luminescence-based assay. Mitochondrial respiration and glycolysis were measured by the Seahorse Bioscience XFe 96 Extracellular Flux Analyzer. Protein levels were analyzed by western blot analysis. Results: GM prevented glutamate-induced cytotoxicity in an HT-22 neuronal cell line even with a 9-hour exposure delay. GM blocked glutamate-induced intracellular ROS accumulation through suppressing mitochondrial respiration. Further, we found that GM up-regulated glycolysis and the pentose-phosphate pathway, which is involved in the production of intracellular reducing agent, NADPH. In addition, GM protected primary cortical neurons from both glutamate and buthioninesulfoximine toxicity. Conclusion: GM prevents glutamate-induced oxidative damage through reducing mitochondrial respiration, which further suppresses ROS generation. In addition, GM up-regulates glycolysis which compensate for the energy depletion induced by mitochondrial respiration inhibition. Overall, our study is the first to report that GM protects neurons from oxidative toxicity by shifting energy metabolism from mitochondrial respiration to glycolysis. Graphical abstract: